Review on Performance of Dual Mass Flywheel over Conventional Flywheel - Dhanashree S. Ware, Dattatray P. Kamble, Kashinath H. Munde, Vikas K. Mehtre (Mathematical Statistician and Engineering Applications, 2022)
The Dual Mass Flywheel is used for dampening the oscillations created at the time of working in automotive power transmission system.Dual mass flywheel is a multi-clutch device. The torsional frequency is defined as the rate at which the torsional vibration produced. When the torsional frequency of the crankshaft is equal to the transaxles torsional frequency an effect known as the torsional resonance occurs. When the operating speed of the engine is minimum, vibration occurs due to the torsional resonance and this can be avoided using dual mass flywheel.We explained detailed initial model in the paper. In this mainly having the two arc springs and two masses in the DMF and their nature. By experiment the Dual Mass Flywheel model is compared to convention flywheel. Finally the observation of the engine torque using the DMF is taken. The DMF is manufactured and done experiment or testing to see the results. And then results which came are compare with the conventional flywheel.